Posterior Fossa Abnormalities in Infantile Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Previously published cerebellar vermis measures of 78 autistic patients from 4 separate MRI studies have been reanalysed at the Neurosciences Department, School of Medicine, University of California at San Diego, La Jolla, CA.